2013
DOI: 10.1890/12-0519.1
|View full text |Cite|
|
Sign up to set email alerts
|

Cessation of a salmon decline with control of parasites

Abstract: The resilience of coastal social-ecological systems may depend on adaptive responses to aquaculture disease outbreaks that can threaten wild and farm fish. A nine-year study of parasitic sea lice (Lepeophtheirus salmonis) and pink salmon (Oncorhynchus gorbuscha) from Pacific Canada indicates that adaptive changes in parasite management on salmon farms have yielded positive conservation outcomes. After four years of sea lice epizootics and wild salmon population decline, parasiticide application on salmon farms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 66 publications
3
42
0
Order By: Relevance
“…The natural process of migratory allopatry, where uninfected juvenile salmon are separated from adult salmon and protected from sea lice by migration [39], can be interrupted by the presence of sea louse reservoirs on salmon farms. When these reservoirs were removed by fallowing or parasiticide treatment of farmed salmon, epizootics of sea lice on wild juvenile salmon declined [40], helping to verify model predictions.…”
Section: Outbreak and Transmission Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural process of migratory allopatry, where uninfected juvenile salmon are separated from adult salmon and protected from sea lice by migration [39], can be interrupted by the presence of sea louse reservoirs on salmon farms. When these reservoirs were removed by fallowing or parasiticide treatment of farmed salmon, epizootics of sea lice on wild juvenile salmon declined [40], helping to verify model predictions.…”
Section: Outbreak and Transmission Dynamicsmentioning
confidence: 99%
“…In spawner-recruitment models, a population's growth rate during sea louse epidemics can be compared to the population growth rate of the same population before or after the epidemic, or to nearby, unexposed salmon populations (figure 5b). Studies on wild pink (Oncorhynchus gorbuscha) [13,24,40] and coho (Oncorhynchus kisutch) [25] salmon in Pacific Canada found evidence that population growth rates are depressed in populations exposed to sea lice outbreaks associated with salmon aquaculture. Similarly, studies on post-smolt wild sea trout (Salmo trutta) in Ireland found that infection levels were higher if the fish were captured in bays that also contained salmon farms [46].…”
Section: Implications For Conservation and Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea cage aquaculture causes sea lice on sympatric wild fish to increase (Frazer 2009). Marine survival of wild pink salmon has been related negatively to lice density on farmed salmon (Marty et al 2010, Krkošek et al 2011 and to observed lice infestation on out-migrating juvenile wild fish (Peacock et al 2013). The negative impact of sea lice on salmonid survival appears to be exacerbated by warmer environmental conditions (Bateman et al 2016, Shephard et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of sea lice to overall marine survival of wild Atlantic salmon re mains an important knowledge gap, particularly in the context of changing oceanographic conditions and the long-term decline of many populations. Parsing out coastal sea lice effects might contribute to understanding of changing high-seas marine survival, and possibly guide management of lice on salmon farms to reduce impacts on wild populations (Peacock et al 2013).…”
Section: Introductionmentioning
confidence: 99%